USE OF BIOMETRIC TECHNOLOGY AND INCLUSION OF MARGINALISED COMMUNITIES IN FOOD SECURITY PROGRAMS - Pandit , Jagriti (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2023)
This paper presents research on the technological applications and its relation with the poverty alleviation programs especially the use of biometrics. One of these programs which is currently undergoing on the issue of food security in Jharkhand, is the Public Distribution System (PDS) and its transformation through technologies. The Public Distribution System is the backbone of India’s food security programs. Today, biometric identification is widely used in ration shops around the nation. The aim of the paper is the assessment of biometric technology in the Public Distribution System (PDS) and the inclusion of marginalized communities within that particularly the tribal people. This paper illustrates the transformative power of using Digital Public Infrastructure (DPIs) for food security schemes and leads to the inclusion of vulnerable communities at large, especially during adverse situations of the pandemic. The system helped combat food grain diversion mafias at large and ensured inclusivity of marginalised sections of the people within the PDS system. The paper not only advocates the need of these digital mechanisms for the smooth functioning of social security programs but it also critically articulates such provisions. It looks upon the technological advancements which our society currently requires for development but also highlights the limitations coming with it which cannot be denied. The introduction of biometric technology to the PDS has rebuilt it into one of the robust mechanisms which identify the beneficiary, regulate the shops, and bring transparency to the system, warding off bogus ration card holders and other malpractices.